PENGARUH MOTIVASI KERJA KEPALA SEKOLAH TERHADAP KUALITAS PENERAPAN MANAJEMEN BERBASIS SEKOLAH - Salmiyanti, Salmiyanti (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The principal is a functional teacher who is given the task the task of leading a school where the learning process is held teaching or a place where there is interaction between the teacher who gives lessons and students who receive lessons. With this the Principal can be regarded as a leader in the educational unit that runs it carry out the management of the led education unit. At the operational level, the school principal is the party at the forefront of coordinating efforts touimprove theyquality of learning. This studyeaims to explore the influenceyof school principals' work motivationyon the quality of school-based management implementation. This type of research is quantitative. The population in this study were students of MIN 3 Padang City, as many as 100 students. Based on the calculation, a research sample of 50 people was obtained. The results showedythat the t value was 3.766 and the t table value was 1.161 (t count > t table). Then the significance t valueyof 0.002 is smaller than the significant influence on the quality of implementing school-based management. In the multi-variable-correlation analysis test, it can beyseen that the workymotivation of school principals has a positiveyinfluence on the quality of implementing school-based management.